EDUKASI KESEHATAN JIWA PONDOK PESANTREN MELALUI PENDEKATAN MANAJEMEN STRES - Alfianto, Ahmad; Illahi Adi Putra, M.Arizki; Ayu Novi ambarwati, Arista Ayu; Azriel Hadianto, Jefri (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2025)
This study emphasizes the importance of mental health among students in Islamic boarding schools (pondok pesantren), who often face various academic and social pressures. According to the World Health Organization (WHO), mental health is defined as a state in which individuals feel happy and healthy, are capable of facing life's challenges, and maintain a positive attitude towards themselves and others. The objective of this research is to evaluate the effectiveness of stress management-based education on the mental health of students at Pesantren X. A quantitative pre-experimental design was employed, involving 28 students selected through purposive sampling. The DASS-42 questionnaire was utilized to assess mental health before and after the intervention. Results indicated that post-education, 64.3% of students exhibited normal levels of depression, 53.6% showed normal anxiety, and 67.9% reported normal stress levels. The Wilcoxon test yielded a p-value of 0.000 (p < 0.05), indicating a significant effectiveness of the educational program. The findings affirm that mental health education through stress management is effective in enhancing both the mental health and knowledge of students. Therefore, it is recommended that Islamic boarding schools incorporate this program into their curriculum to support the psychological well-being of their students.